Prognostic significance of the HFA‐PEFF score in patients with heart failure with preserved ejection fraction - Yohei Sotomi (ESC Heart Failure, 2021)
Abstract Aims The HFA‐PEFF score is a part of the stepwise diagnostic algorithm of heart failure with preserved ejection fraction (HFpEF). We aimed to evaluate the prognostic significance of the HFA‐PEFF score on the clinical outcomes in patients with HFpEF. Methods and results The Prospective mUlticenteR obServational stUdy of patIenTs with Heart Failure with preserved Ejection Fraction (PURSUIT‐HFpEF) study is a prospective, multicentre, observational study in which collaborating hospitals in Osaka record clinical, echocardiographic, and outcome data of patients with acute decompensated heart failure with preserved left ventricular ejection fraction (≥50%) [UMIN‐CTR ID: UMIN000021831]. Acute decompensated heart failure was diagnosed on the basis of the following criteria: (i) clinical symptoms and signs according to the Framingham Heart Study criteria; and (ii) serum N‐terminal pro‐B‐type natriuretic peptide level of ≥400 pg/mL or brain natriuretic peptide level of ≥100 pg/mL. The HFA‐PEFF score has functional, morphological, and biomarker domains. We evaluated the prognostic significance of the HFA‐PEFF score (calculated based on the data at hospital discharge) on post‐discharge clinical outcomes in this cohort. The primary endpoint of the present study was a composite of all‐cause death and heart failure readmission. Between June 2016 and December 2019, 871 patients were enrolled from 26 hospitals (mean follow‐up duration 399 ± 349 days). A total of 804 patients were finally analysed after excluding patients with scores of 0 (N = 5) and 1 (N = 15) from 824 patients with available HFA‐PEFF score based on the echocardiographic and laboratory data at discharge. According to the laboratory and echocardiographic data at the time of discharge, 487 patients (59.1%) were diagnosed as HFpEF (HFA‐PEFF score ≥ 5) while 317 patients (38.5%) had intermediate score. Kaplan–Meier analysis divided by the HFA‐PEFF score [low, score 2–5 (N = 494) vs. high, score 6 (N = 310)] indicated that the HFA‐PEFF score successfully stratified the patients for the primary endpoint (log‐rank test P < 0.001). Cox proportional hazard model showed that the HFA‐PEFF score was significantly associated with the primary endpoint (high score with reference to low score, adjusted hazard ratio 1.446, 95% confidence interval [1.099–1.902], P = 0.008). Conclusion The HFA‐PEFF score at discharge was significantly associated with the post‐discharge clinical outcomes in acute decompensated heart failure patients with preserved ejection fraction. This study suggested clinical usefulness of the HFA‐PEFF score not only as a diagnostic tool but also a practical prognostic tool.